Efektivitas Penyuluhan Kesehatan Dalam Peningkatan Kesadaran Kesehatan Lingkungan Pada Wilayah Kerja PUSTU Tanjung Dalam Kecamatan Pondok Kubang - Mulyadi Mulyadi (STIA Bengkulu, 2022)
The aim of this study was to describe, explain and analyze the effectiveness of health educators in raising awareness about environmental health in the work area of ​​PUSTU Tanjung in Pondok Kubang district. The title of this study is “Efficacy of health extension in raising environmental health awareness in the Pustu Tanjung work area in Pondok Kubang district”. The method used in this study belongs to the type of qualitative descriptive research. Data for this study were collected through observation and interview techniques. The sample for this study consisted of pustu health educators and a community sample determined by simple random sampling, where the sample taken was representative of 10% of the total number of existing heads of households, up to family in Tanjung Dalam village Pondok Kubang District. Based on the results of the study, it can be concluded that the implementation of health educators aims to increase awareness of environmental health at Tanjung Pustu work area in Pondok Kubang district. Ineffective, indicated by the lack of public awareness of the importance of environmental health. It can be seen that this is because many people are still not aware of the importance of environmental health, people are not aware of improper waste treatment, often throw garbage behind the house and bury their feces, ordinary people let water stagnate, dry clothes and garbage, there are still many people who do not handle their waste in a healthy way, some people still throw garbage everywhere, there are still people who throw garbage in the river, and there are still many people who do not have a home Hygiene, reasonable family toilet.